Evaluation and stability analysis of recently released mesoamerican red-colored common bean (Phaseolus vulgaris L.) varieties in the Southern Ethiopia region - Bassa Belayneh, Demelash (Food Agricultural Sciences and Technology, 2025)
The small red Phaseolus vulgaris L. varieties were tested at three sites from 2022 to 2023 (six environments, E1 to E6) to evaluate and select superior and stable varieties. A randomized complete block design was used to evaluate six varieties with four replications. The varieties were planted in six rows per plot; the space between rows, plants, plots, and reps were 0.4 m, 0.1 m, 0.8 m, and 1 m, respectively. ANOVA showed significant differences (P < 0.01) for seed yield (kg ha⁻¹), days to 50% flowering, days to 90% maturity, plant height (cm), seed per pod, and pod per plant both at individual environments and in the combined analysis. The GEI (Genotype by Environment Interaction) was significant (P < 0.01) for the measured traits. The mean seed yield in the three sites was 2,397.5 kg ha⁻¹. The superior varieties were SER 119 and SER 125 with a mean seed yield of 2,846 and 2,639 kg ha⁻¹ respectively; however, the most stable genotype identified by AMMI and GGE bi-plots was SER 125. The AMMI ANOVA showed that environments, genotypes, and their interaction were significant; and their magnitude was 31.85%, 14.75%, and 27.75% respectively of the total variation. Besides, the study identified discriminating (Bolosso Bombe and Areka) and undiscriminating (Gofa) environments. Hence, this study recommended that SER 125 and SER 119 common bean varieties could be produced in the tested locations and areas with similar agro-ecological zones.